2007
DOI: 10.1038/nprot.2007.210
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased identification of cysteine S-nitrosylation sites on proteins

Abstract: Covalent addition of nitric oxide (NO) to Cys-sulfur in proteins, or S-nitrosylation, plays pervasive roles in the physiological and pathophysiological modulation of mammalian protein functions. Knowledge of the specific protein Cys residues that undergo NO addition in different biological settings is fundamental to understanding NO-mediated signal transduction. Here, we describe in detail an MS-based proteomic protocol for facile, high-throughput and unbiased discovery of SNO-Cys residues in proteins from com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 11 publications
0
60
0
3
Order By: Relevance
“…This false positive rate compares favorably with the greater than 90% specificity reported for immobilized metal affinity chromatography used for the enrichment of phosphopeptides from mouse liver (14). Therefore, pretreatment with UV served as negative control throughout based on previous studies that documented the elimination of S-nitrosocysteine without affecting other cysteine modifications (15,16). Collectively, these experiments showed that the reaction of protein Snitrosocysteine with the phenylmercury compounds is specific and efficient and achieved selective identification of the modified residue, the ultimate qualifier for the unambiguous assignment of Snitrosylated proteins through the inclusion of negative controls.…”
Section: Resultsmentioning
confidence: 87%
“…This false positive rate compares favorably with the greater than 90% specificity reported for immobilized metal affinity chromatography used for the enrichment of phosphopeptides from mouse liver (14). Therefore, pretreatment with UV served as negative control throughout based on previous studies that documented the elimination of S-nitrosocysteine without affecting other cysteine modifications (15,16). Collectively, these experiments showed that the reaction of protein Snitrosocysteine with the phenylmercury compounds is specific and efficient and achieved selective identification of the modified residue, the ultimate qualifier for the unambiguous assignment of Snitrosylated proteins through the inclusion of negative controls.…”
Section: Resultsmentioning
confidence: 87%
“…Detection of S-Nitrosated Proteins by Biotin Switch Assay-SNOmodifications were detected in GSNO treated mitochondrial lysates using the biotin switch assay described in (21) (discussed in (17,19,21,26)), see Captured proteins were eluted with 40 L of elution buffer containing 100 mmol/L DTT, mixed with 15 L of 4ϫ LDS sample buffer, boiled, separated by SDS-PAGE (4 -12%) and silver stained according to the protocol described in (27).…”
Section: Methodsmentioning
confidence: 99%
“…6 Switch Assay-SNO-modifications were detected in GSNO treated HPAEC lysates using the biotin switch assay (12,14) (discussed in (14,16,25), see Fig. 1A for reaction schema).…”
Section: In Vitro Detection Of S-nitrosylated Proteins By Biotin/cystmtmentioning
confidence: 99%